The Pelaksanaan Proyek Memasak dalam Model Project Based Learning (PjBL) untuk Meningkatkan Kreativitas Siswa pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMA N 2 IV Koto Kab. Agam - sari, Indah; Muliati, Indah (Lembaga Yasin AlSys, 2025)
The limited research on the application of the Project-Based Learning (PjBL) model in Islamic Religious Education (PAI) has become a significant concern, as it contributes to low student creativity and a lack of practical understanding of religious values in daily life. This study aims to analyze the implementation of the PjBL model through a cooking project and its impact on enhancing students’ learning creativity in PAI. A qualitative descriptive approach was employed, involving five participants (one teacher and four students) selected through purposive sampling. Data were collected via participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that implementing PjBL through a cooking project effectively enhances student creativity across four key indicators: fluency, flexibility, originality, and elaboration. These results align with constructivist theory and PjBL pedagogical principles, demonstrating that cooking projects can serve as an innovative method for linking theory with practice in PAI learning. The study's implications include a theoretical contribution to the literature on PjBL effectiveness in the PAI context and practical recommendations for PAI teachers to develop contextual, project-based instructional methods. Additionally, this research opens pathways for further studies on project duration and group arrangement strategies to optimize student creativity.